Regulation of the cytochrome P450 epoxyeicosanoid pathway is associated with distinct histologic features in pediatric non-alcoholic fatty liver disease. (January 2021) - Kalveram, Laura; Schunck, Wolf-Hagen; Rothe, Michael; Rudolph, Birgit; Loddenkemper, Christoph; Holzhütter, Hermann-Georg; Henning, Stephan; Bufler, Philip; Schulz, Marten; Meierhofer, David; Zhang, Ingrid W.; Weylandt, Karsten H.; et al.
Highlights: Fatty acid profiles of obese pediatric patients with biopsy-proven NAFLD exhibit typical features of Western diet. Epoxyeicosanoid levels are upregulated with higher grades of steatosis due to increased CYP450 epoxygenase activity and reduced activity of soluble epoxide hydrolase. Fibrosis-associated downregulation of epoxyeicosanoid formation was significant in patients with both high grades of steatosis and fibrosis due to decreased CYP450 epoxygenase activity. Supplementation of the respective essential PUFA precursors, direct administration of synthetic epoxyeicosanoids as well as inhibition of soluble epoxide hydrolase may represent potent pharmacologic strategies in the treatment of NAFLD. Abstract: Non-alcoholic fatty liver disease (NAFLD) is a significant health burden in obese children for which there is currently no specific therapy. Preclinical studies indicate that epoxyeicosanoids, a class of bioactive lipid mediators that are generated by cytochrome P450 (CYP) epoxygenases and inactivated by the soluble epoxide hydrolase (sEH), play a protective role in NAFLD. We performed a comprehensive lipidomics analysis using liver tissue and blood samples of 40 children with NAFLD. Proteomics was performed to determine CYP epoxygenase and sEH expressions. Hepatic epoxyeicosanoids significantly increased with higher grades of steatosis, while their precursor PUFAs were unaltered. Concomitantly, total CYP epoxygenase activity increased while protein level and activity of sEH decreased. In contrast, hepatic epoxyeicosanoids showed a strong decreasing trend with higher stages of fibrosis, accompanied by a decrease of CYP epoxygenase activity and protein expression. These findings suggest that the CYP epoxygenase/sEH pathway represents a potential pharmacologic target for the treatment of NAFLD.